Pengaruh Biaya Promosi Terhadap Hasil Penjualan Sepeda Motor Pada Dealer Tunas Dwipa Matra Mojosari - Ichwan Bagus Airlangga; Syahrul Reynaldy (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
Marketing is the main function of the company's success in obtaining revenue and profits from the sale of its products. so that it can be calculated that the survival of the company depends on the marketing strategy policies set by the company. In addition to the marketing strategy policy, the resources owned are mobilized to be able to achieve the goals or targets set by management after the market share is obtained. Sales volume is a means for the development of a new brand marketed by the company. Companies that are only marketers are also required to be able to design and implement marketing strategies that are able to create, maintain, and increase sales results. Keywords: Marketing ; Income ; Product; Management; Strategy.